Pengaruh E-Commerce dan Efektivitas Kerja Pengguna Terhadap Kinerja Perusahaan Pada Usaha Kecil dan Menengah di Denpasar - Sarastyarini, Ni Made Werin; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
The purpose of this study is to determine the effect of e-commerce and effectiveness of the user'swork on the company's performance on small and medium enterprises in Denpasar. The sampletaken is 88 of 766 SMEs using e-commerce in Denpasar. The sample in this research is determinedby probability sampling method with simple random sampling technique. Data collection was donethrough survey obtained by distributing questionnaires to the respondents. Respondents in thisstudy are business actors. Analytical technique used multiple linear regression with SPSS 22.0software. The results showed that the performance of companies in small and medium enterpriseswill increase if the business actors using e-commerce in running and developing business andimprovement on the effectiveness of e-commerce users will be followed also by improving theperformance of companies in small and medium enterprises tha t use e- commerce in Denpasar. Keywords : E-Commerce, User Work Effectiveness, Corporate Performance